Pengaruh Pengetahuan Lingkungan terhadap Sikap dan Perilaku Konsumen dalam Memilih Produk Ramah Lingkungan: Studi Kasus Mahasiswa Universitas Negeri Medan - Purba, Bonaraja; Siboro, Hotman; Sianturi, Tasya; Banjar, Yefoni Valentina; Situmeang, Venus (Economic Reviews Journal, 2024)
This study aims to uncover the impact of environmental knowledge on consumer attitudes and behaviors in selecting environmentally friendly products, especially among students at Universitas Negeri Medan. A quantitative analysis method was applied by collecting data through online surveys using Google Forms, involving 35 randomly selected respondents from various faculties. The analysis was conducted using the Statistical Package for the Social Sciences (SPSS) software, confirming that environmental knowledge significantly influences consumer attitudes and behaviors. These findings emphasize the importance of environmental knowledge in shaping environmentally conscious attitudes and behaviors among consumers, particularly among students. Furthermore, this research identifies consumer attitudes as a mediator in the relationship between environmental knowledge and consumer behavior. Based on these results, it is recommended to develop comprehensive environmental education programs, conduct further research on other influencing factors, collaborate with industries, develop supportive campus policies, and launch environmental awareness campaigns. These steps are expected to enhance awareness and consumer behavior regarding environmentally friendly products among students and provide directions for further research in this field.